الادارة بالشفافية كآلية لمكافحة الفساد الاداري في الجزائر - دبوب, ايمان; حروشي, نسيمة (University of Eloued جامعة الوادي, 2020)
إن الشفافية والفساد الاداري مفهومان متعاكسان في الاتجاه ولا يلتقيان أبادا، وإن حل أحدهم ببلد ما عمل بكل جهد ومثابرة على طرد الآخر، والفرق بينهما هو أن الشفافية تعد أحد العناصر الفعالة التي تسهم في تنمية الدول، وتنمي خدماتها، وتساعد على نشر الرخاء والسعادة في المجتمع الذي تحل به، بينما الفساد إذا ما انتشر بأي دولة أنهك قواها الاقتصادية، ودمر بُن اها التحتية، وساهم في تفكيك أصولها الاجتماعية والثقافية. تهدف هذه الد ا رسة إلى معرفة مدى مساهمة الادارة بالشفافية في الحد من الفساد الادا ري ومكافحته في التشريع الج ا زئري .Transparency and administrative corruption are controversial concepts and they could never meet. When one of them settles in a country it expels the other. The difference between them is that transparency is one of the active elements that contribute to the development of countries, develop their services, help spread prosperity and happiness in the society they solve, while corruption, if entrenched in any country it exhausts its economic forces, destroys its infrastructure and contributes to the dismantling of its social assets And cultural activities. This study aims to know the extent to which the administrative transparency in reducing and combating the administrative corruption in the Algerian legislation.
مذكرة ماستر
Keywords: الشفافية الادارية، الفساد الاداري ، وسائل مكافحة الفساد، مظاهر الفساد .; administrative transparency, administrative corruption, appearances of corruption, anti-corruption methods.